New perspectives on crime and criminal justice - Sarat, Austin (Bingley, UK : Emerald Group Pub., 2009)
This volume of "Studies in Law, Politics, and Society" contains a Special Issue on crime and criminal justice. It brings together the work of scholars whose work usefully illuminates central questions in about how we define and process those who violate the criminal law and about the technologies of policing and punishment. The articles published here exemplify the exciting and innovative work now being done in interdisciplinary legal scholarship.
Includes bibliographical references.
Description based on print version record.
Keywords: Crime prevention -- United States; Imprisonment -- United States; Bail -- Pennsylvania -- Philadelphia; Criminal justice law; Law -- Criminal Law -- General